International Trade Statistics Yearbook 2014, Volume I - United Nations Department of Economic; Social Affairs (United Nations, 2014)
The 2014 International Trade Statistics Yearbook (2014 ITSY) is the sixty-third edition of this yearbook. Its objective is to inform about the detailed merchandise and services imports and exports of individual countries (areas) by commodity and service category and by partner country (volume I), the world trade in individual commodities (3-digit SITC groups) (volume II) and total world merchandise trade - up to the year 2014.